The problem of odor research in the scientific literature (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
Different perceptions definition explains the diversity of approaches and specific industry that it is considering. Problems of perception actively investigated physiologists, psychologists, philosophers. Aroma in European culture analyzed in the works of cultural history, aesthetics, linguistics, literature. Odor is the subject of a number of research disciplines: philosophy anthroponymy, philosophy, culture, education, psychology, psychophysics, medical practice. Scientists investigating the phenomenon as a cultural flavor component odoratyvnoho segment of the world, forms its sensory representation peculiarities of perception and information odoratyvnoyi in European culture, science and philosophy.The authors consider the whole system of perception and of particular relevance to smell like a promising direction and interpret flavor not only as an aesthetic phenomenon, but as a «spiritual» segment of the culture of the nation. The matter well represented in a number of scientific studies in the field of linguistics, art. Uzayemopronyknennya explains different types of art practice synestetychnoho use the vocabulary of the senses. This helps in the interpretation of olfactory marks, recognizing odoratyvnyh meaning that enriches human understanding of the world. Smell – a particular property of this or that reality is reflected in modern minds through the olfactory sensations. His influence, a variety of experiences reflected in the language. In the scientific literature odor understood as a feeling that arises during the odorous substances to the receptors of the mucous membrane of the nasal cavity. Characteristic odor usually served by a substance that causes this feeling.
Keywords: odor perception; sensing; smell; flavor vocabulary odorativity component